Targeted co-delivery nanosystem based on methotrexate, curcumin, and PAMAM dendrimer for improvement of the therapeutic efficacy in cervical cancer - Ayuob Aghanejad; Shiva Kheiriabad; Maryam Ghaffari; Simin Namvar Aghdash; Neda Ghafouri; Jafar Ezzati Nazhad Dolatabadi; Hashem Andishmand; Michael R. Hamblin (Scientific Reports)
Abstract The simultaneous administration of multiple drugs within identical nanocarriers to cancer cells or tissues can result in the effective action of drugs at reduced concentrations. In this investigation, PAMAM dendrimers (G4-PAMAM) were employed to link with methotrexate (MTX) using DCC/NHS chemistry and followed by the entrapment of curcumin (Cur) within it. The establishment of covalent bonds between MTX and the PAMAM dendrimer led to PAMAM-MTX interaction, verified and described through FT-IR. Various techniques were employed to evaluate the structural properties of the prepared Cur-PAMAM-MTX NC. The Cur-PAMAM-MTX NC, after preparation, exhibited a particle size of 249 nm, with an encapsulation efficiency (EE) of ~ 81% for Cur. The cumulative in vitro release of Cur-loaded NC indicated a controlled release influenced by time and pH. The cell study results revealed that Cur-PAMAM-MTX NC exhibited significantly higher cytotoxicity than free MTX, Cur, and other formulations tested in vitro. The synergistic effect of co-delivery of MTX and Cur by PAMAM significantly increased cytotoxicity. Besides, the significant ROS level rising has been shown in the treated cells with MTX-PAMAM-Cur. Considering these findings, the co-delivery NC shows promise for additional in vitro investigations and possesses the capacity to function as an effective framework for the combined delivery of MTX and Cur in cervical cancer chemotherapy.